A Cryogenic CMOS-based Control System for Testing Superconductor Electronics - Van Niekerk, Philip Charl (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electical and Electronic Engineering))--University of Stellenbosch, 2008.